Non-ventilation during early incubation in combination with dexamethasone administration during late incubation: 1. Effects on physiological hormone levels, incubation duration and hatching events - Tona, K.; Onagbesan, O.; Bruggeman, V.; De Smit, L.; Figueiredo, D.; Decuypere, E. (Elsevier B.V., 2007)
This study investigated the effect of non-ventilation of the incubator during the first 10 days of incubation and its combination with dexamethasone administration at day 16 or 18 of incubation on hatching parameters and embryo and post-hatch chick juvenile physiology. A total of 2400 hatching eggs produced by Cobb broiler breeders were used for the study. Blood samples were collected at day 18 of incubation, at internal pipping stage (IP), at the end of hatch (day-old chick) and at 7-daypost-hatch for T-3, T-4 and corticosterone levels determination. From 448 to 506 h of incubation, the eggs were checked individually in the hatcher every 2 h for pipping and hatching. The results indicate that non-ventilation during the first 10-day shortened incubation duration up to IP, external pipping (EP) and hatch, had no effect on hatchability and led to higher T-3 levels at IP but lower corticosterone levels at 7-day-post-hatch. The injection of dexamethasone at days 16 and 18 of incubation affected hatching and blood parameters in both the ventilated and non-ventilated embryos differentially and the effect was dependent on the age of the embryo. Dexamethasone increased T-3 levels and T-3/T-4 ratios but the effect was greater with early non-ventilation of eggs. Dexamethasone decreased hatchability but the effect was greater when injected at day 16 and especially in ventilated embryos. The effects of incubation protocols and dexamethasone treatments during incubation were still apparent in the hatched chicks until 7 days of age. The changes in T-3, T-4 and corticosterone levels observed in response to the early incubation conditions and late dexamethasone treatments in this study suggest that incubator ventilation or non-ventilation may influence the hypothalamic-pituitary-adrenal axis (HPA) regulation of stress levels (in terms of plasma corticosterone levels) and thyroid function in the embryo with impact on incubation duration, hatching events and early post-hatch life of the chick. Our results also suggest that some stages of development are more sensitive to dexamethasone administration as effects can be influenced by early incubation protocols. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: chick embryo; incubation; ventilation; dexamethasone; hormone levels